OVERVIEW OF ATHLETIC SPORTS ACHIEVEMENT DEVELOPMENT IN INDONESIA (Qualitative: Comparing and SWOT Analyze) - Kurniawan, Dennis Dwi; Mulyaningsih, Farida; Wulandari, Putri Prastiwi (Universitas Negeri Yogyakarta, 2025)
Olahraga atletik merupakan ladang medali dalam kejuaraan multievent nasional maupun internasional. Sedangkan pembinaan di Indonesia masih menjadi perhatian besar oleh pecinta olahraga atletik di seluruh Indonesia, dengan melihat prestasi atletik tidak bisa bersaing di kancah regional dan dunia. Dalam naskah narasi ilmiah ini akan dibahas tentang bagaimana analisis perbandingan dan SWOT terhadap pembinaan prestasi olahraga atletik di Indonesia. Data diambil data analisis kebutuhan secara subjektif atau kualitatif, serta literature review terhadap hasil-hasil kejuaraan serta artikel pribadi dari para pemerhati olahraga atletik di Indonesia dan beberapa Negara Maju seperti Jepang dan Amerika. Hasil dari pembahasan dan Analisa Perbandingan serta analisis SWOT terhadap olahraga atletik di Negara Maju dan di Indonesia, maka dapat disimpulkan bahwa Pembinaan Olahraga atletik di Indonesia masih sangat perlu mengadopsi berbagai sistem pembinaan secara terstruktur dan tetap melihat kondisi SDM dan geografis di Indonesia. Perlu adanya kebijakan baru yang inovatif dan tepat sasaran dari KONI, Menpora, PASI Pusat dimulai dari sistem pencarian bakat, pembinaan prestasi di lingkungan terbawah sampai pusat yang teorganisir, serta sistem kompetisi yang berkelanjutan. OVERVIEW OF ATHLETIC SPORTS ACHIEVEMENT DEVELOPMENT IN INDONESIA (QUALITATIVE: COMPARING AND SWOT ANALYZE) AbstractsAthletics is a medal field in national and international multi-event championships. Meanwhile, coaching in Indonesia is still a big concern for athletic sports lovers throughout Indonesia, seeing that athletic achievements cannot compete in the regional and world arenas. In this scientific narrative text, a comparison and SWOT analysis will be discussed on the development of athletic sports achievements in Indonesia. The data is taken from subjective or qualitative needs analysis data, as well as literature reviews of championship results as well as personal articles from observers of athletic sports in Indonesia and several developed countries such as Japan and America. The results of the discussion and Comparative Analysis and SWOT analysis of athletic sports in developed countries and in Indonesia, it can be concluded that the development of athletic sports in Indonesia still needs to adopt various structured coaching systems and keep in view the condition of human resources and geography in Indonesia. There is a need for innovative and targeted new policies from KONI, Menpora, PASI Center starting from the talent search system, fostering achievement in the lowest environment to an organized center, and a sustainable competition system.